Blue box. Volume 7 - Miura, Kouji (Manga author) (Shonen Jump manga., 2023)
A badminton guy falls for a basketball girl. Do these sports-crossed lovers have a chance? Taiki Inomata loves badminton, but he has a long way to go before he can reach nationals. When Taiki sees upperclassman Chinatsu Kano practicing her heart out on the girls' basketball team, he falls for her hard. After an unexpected turn of events brings the two closer together, sports might not be the first thing on their minds anymore! Taiki participates in a practice match against Sajikawa High School and faces off against Yusa, the rising star who dashed his hopes of attending nationals. To put the past behind him, Taiki must power through and battle his badminton demons head-on!